دور الانشطة اللاصفية في تحقيق التفاعل الايجابي لتلميذ المرحلة الابتدائية في المحيط المدرسي - علي مود; عبلة سيدي عثمان (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة الى التعرف على دور الأنشطة اللاصفية في تحقيق التفاعل الإيجابي لتلميذ المرحلة الابتدائية في المحيط المدرسي، حيث تم طرح التساؤل الرئيسي التالي: هل تساهم الأنشطة اللاصفية في تحقيق التفاعل الإيجابي لتلميذ المرحلة الابتدائية في المحيط المدرسي؟ الذي اندرجت تحته التساؤلات الفرعية التالية: - هل تساهم الأنشطة اللاصفية الرياضية في تحقيق التفاعل الإيجابي لتلميذ المرحلة الابتدائية في المحيط المدرسي؟ - هل تساهم الأنشطة اللاصفية الثقافية والاجتماعية في تحقيق التفاعل الإيجابي لتلميذ المرحلة الابتدائية في المحيط المدرسي؟ - هل تساهم الأنشطة اللاصفية البيئية والتطوعية في تحقيق التفاعل الإيجابي لتلميذ المرحلة الابتدائية في المحيط المدرسي؟ وهدفت الدراسة الى: - التعرف على مدى فاعلية الأنشطة اللاصفية في زيادة التفاعل الإيجابي لتلميذ المرحلة الابتدائية. - ابراز أهمية الأنشطة اللاصفية من حيث الدور الذي تحققه في اكساب التلميذ تفاعلا إيجابيا في المحيط المدرسي. - دمج الأنشطة اللاصفية في البرامج التربوية وجعلها جزء محوري يعزز من دور المدرسة اعتمدت الدراسة على المنهج الوصفي باستخدام أسلوب دراسة الحالة بالاعتماد على أداة المقابلة نصف الموجهة والملاحظة المباشرة لجمع البيانات على عينة مكونة من 10 معلمين و40 تلميذ حيث تم التوصل الى النتائج التالية: 1. تؤدي الأنشطة اللاصفية الرياضية دورًا محوريًا ومهما جدا في تنمية التفاعل الإيجابي للتلاميذ، حيث ساهمت بشكل واضح في تعزيز التعاون بين التلاميذ والانضباط والاحترام المتبادل بين التلاميذ، كما ساعدت أيضا في الحد من السلوكيات العدوانية التي كان يظهرها التلاميذ بينهم وتحسين العلاقات الاجتماعية بينهم داخل المحيط المدرسي. 2. للأنشطة اللاصفية الثقافية والاجتماعية أثر واضح وكبير في تنمية المهارات اللغوية للتلاميذ وحصولهم على مدارك معارفية وفكرية واسعة، وبناء الثقة بالنفس، ما اثر مباشرة وانعكس إيجابًا على مشاركتهم وتفاعلهم داخل الصف وتعاملهم داخل محيطهم المدرسي. 3. تعزز الأنشطة البيئية والتطوعية الشعور بالانتماء والمسؤولية للتلميذ تجاه محيطه المدرسي، كما ساهمت ايضا في تكوين قيم في التلاميذ عن النظافة والتعاون واحترام المحيط المدرسي وجهود الاخرين." "Study Summary: This study aims to identify the role of extracurricular activities in achieving positive interaction for elementary school students within their school environment. The following main question was posed: What is the role of extracurricular activities in achieving positive interaction for elementary school students within their school environment? This question was sub-questions: - Do extracurricular sports activities contribute to achieving positive interaction for elementary school students within their school environment? - Do extracurricular cultural and social activities contribute to achieving positive interaction for elementary school students within their school environment? - Do extracurricular environmental and volunteer activities contribute to achieving positive interaction for elementary school students within their school environment? The study aimed to: - Identify the effectiveness of extracurricular activities in increasing positive interaction for elementary school students. - Highlight the importance of extracurricular activities in terms of their role in fostering positive interaction among students within their school environment. - Integrating extracurricular activities into educational programs and making them a pivotal component that enhances the role of the school. The study relied on a descriptive approach using a case study tool, relying on semi-structured interviews and direct observation to collect data from a sample of 10 teachers and 40 students. The following results were obtained: 1. Extracurricular sports activities play a pivotal and very important role in developing positive student interaction. They clearly contributed to enhancing cooperation among students, discipline, and mutual respect among them. They also helped reduce aggressive behaviors among students and improve social relations within the school environment. 2. Extracurricular cultural and social activities have a clear and significant impact on developing students' language skills, acquiring broad cognitive and intellectual knowledge, and building self-confidence. This has a direct and positive impact on their participation and interaction within the classroom and their interactions within the school environment. 3. Environmental and volunteer activities enhance students' sense of belonging and responsibility toward their school environment. They also contribute to instilling values in students about cleanliness, cooperation, and respect for the school environment and the efforts of others"
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع التربية.
Keywords: الأنشطة اللاصفية; التفاعل الإيجابي; المحيط المدرسي; extracurricular activities; positive interaction within; the school environment